Особливості озвучення приміщень з великим часом реверберації - Бречко, Ю. В. (ХНУРЕ, 2020)
This paper analyze the technical decisions on scoring of the big booming premises are investigated. In this work we used mathematical modeling of the sound field and calculation of acoustic parameters in the software environment EASE. We analyzed some criteries of sound clarity: the direct-to-reflect wave intensities ratio (D/ R), the ratio of energy before and after 50 ms (C50), as well Alcons and RASTI options. We investigated three positions of the speakers: chain with inclined acoustic axis, ceiling version with a vertical axis and acoustic cluster speaker placement. Optimum technical decisions are selected.
Keywords: реверберація; озвучення приміщень